EMPOWERING INCLUSIVE SCHOOLS: TRAINING TO PREVENT AND ADDRESS BULLYING OF STUDENTS WITH SPECIAL NEEDS - Muhammad Nurrohman Jauhari; Lutfi Isni Badiah; Ferdiansyah; Afriliansyah (Universitas PGRI Adi Buana Surabaya, 2025)
The implementation of this community service program aimed to provide knowledge on the prevention and management of bullying toward students with special needs. The program was carried out through three main stages: a) planning, b) implementation, and c) evaluation. Based on the results, it can be concluded that the empowerment of inclusive schools through training to prevent and address bullying of students with special needs had a positive impact on teachers. The success of the program is reflected in the improvement of participants' understanding, as evidenced by an increase in the average score from 60.18 in the pre-test to 82.32 in the post-test.